Metacognition Mediates the Relationship Between Maladaptive Personality Traits and Levels of Personality Functioning: A General Investigation on a Nonclinical Sample. Issue 5 (May 2021) - Pedone, Roberto; Barbarulo, Anna Maria; Colle, Livia; Semerari, Antonio; Grimaldi, Pietro
Abstract : Abstract: The impaired ability to reflect on one's own state of mind and that of others (called metacognition or mentalization) is a central feature of personality disorders (PDs). Metacognition involves different specific abilities, which can be selectively impaired with different PDs and personality maladaptive traits. Moreover, research in the field of PDs has indicated that personality features and metacognitive abilities are associated with the severity of personality pathologies. In this study, we tested a mediation model of the interactions between these variables on predicting levels of personality functioning in a sample of adults taken from the general population ( N = 775). Results showed that the relationship between personality traits and personality functioning is partially mediated by metacognitive abilities. These findings support the hypothesis that metacognition plays a significant role in predicting the levels of impairment in personality functioning. These findings have several clinical implications.